Grazers and predators mediate the post-settlement bottleneck in Caribbean octocoral forests - Wells, Christopher D.; Benz, Joseph; Tonra, Kaitlyn J.; Anderson, Emily R.; Lasker, Howard R. (Frontiers in Marine Science, 2024)
In the Caribbean, reef-building scleractinian corals have declined precipitously and octocorals have emerged as one of their main successors. The success of octocorals and the formation of octocoral forests has been attributed to their continuing recruitment to reef habitats, as well as tolerance to pollution, reduced direct competition with scleractinians, and resistance and resilience to climatic events. Benthic grazers on coral reefs can facilitate the growth and recruitment of corals by reducing the abundance of competitive algal turfs and macroalgae. However, grazing can also hinder corals through sublethal damage to coral tissue and predation of recruits. We assessed the effects of grazing by fishes and the sea urchin Diadema antillarum as well as predation by mesofauna on octocoral recruitment through a series of manipulative in situ and ex situ experiments. Exposure to fish and urchin grazing significantly reduced the post-settlement survival of octocoral recruits, while turf-associated mesofauna did not significantly affect recruitment. We also found a positive relationship between octocoral recruitment and the abundance of turf algae, which may reflect the deleterious effect of grazing on both turf algae and octocoral recruits. These data suggest that grazers and predators mediate the bottleneck characteristic of recruitment, primarily through their effect on post-settlement survival. Thus, the declines in the abundance of grazing fishes and urchins throughout the Caribbean may have contributed to the increase in Caribbean octocoral abundance, concurrent with the loss of scleractinians.